Burnout pada Karyawan di Rumah Sakit Selama Wabah COVID-19 - Rohmah, Ulfa Nur; Lipin, Lipin; Rahmaningsih, Ary (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2021)
Background: Burnout during the COVID-19 outbreak has an impact on poor quality of life and the treatment process of patients. Objective: To identify determinant of factors that caused with burnout on staffs in hospital during COVID-19 outbreak. Metodh: The databased used was Scopus, Science Direct, CINAHL, Pubmed, Proquest from January 2020-May2021. The keywords used in this study were burnout syndrome or burnout or burn out or burn-out AND healthcare workers or medical workers or healthcare professionals AND pandemic or COVID-19 or coronavirus. Results: This study reviewed 17 articles. The questionnaire used Maslach Burnout Inventory (MBI). Demographic characteristics, various conditios related to COVID-19, psychological state and resilience have contributed to affect burnout of emlployees in hospital. Conclusion: It is necessary to develop an intervention or idea to manage burnout during the COVID-19 outbreak so can contributet patient care and reduce mortality